Exploration of a mixture of HMR (high moisture resistant) and HDPE (high-density polyethylene) as an environmentally friendly furniture board alternative - Kusbijanto, Ancilla Domini; Pambudi, Terbit Setya; Azhar, Hanif (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Waste management remains a significant obstacle to sustainable living, particularly due to the accumulation of plastic waste at disposal sites and the furniture industry’s growing reliance on unsustainable plywood materials. Annually, over 300 million tons of plastic waste are generated. High-Density Polyethylene (HDPE) plastic waste, often containing formaldehyde resin, and moisture-resistant (HMR) board waste are frequently discarded without proper processing, posing environmental concerns. Despite their valuable properties—HMR offers moisture resistance, while HDPE provides strength and recyclability—limited research exists on their synergistic application in sustainable composite materials. This study explores the integration of HDPE and HMR as an environmentally responsible alternative to conventional furniture boards. Employing a qualitative approach, including observation, expert interviews, and literature analysis, combined with a thermopressing methodology, the study identifies optimal mixing techniques for producing boards resistant to heat, humidity, and substantial loads. Three composition ratios were tested: 200:50, 190:60, and 180:70 (HDPE to HMR). Results demonstrate that the 200:50 composition achieved optimal performance, withstanding 23 kg loads without failure, exhibiting excellent water resistance over 24 hours, and showing superior fire resistance compared to conventional plywood. This research contributes to waste valorization and sustainable material innovation for furniture manufacturing.